2022
DOI: 10.3390/toxics10050264
|View full text |Cite
|
Sign up to set email alerts
|

Simulating PM2.5 Concentrations during New Year in Cuenca, Ecuador: Effects of Advancing the Time of Burning Activities

Abstract: Fine particulate matter (PM2.5) is dangerous to human health. At midnight on 31 December, in Ecuadorian cities, people burn puppets and fireworks, emitting high amounts of PM2.5. On 1 January 2022, concentrations between 27.3 and 40.6 µg m−3 (maximum mean over 24 h) were measured in Cuenca, an Andean city located in southern Ecuador; these are higher than 15 µg m−3, the current World Health Organization guideline. We estimated the corresponding PM2.5 emissions and used them as an input to the Weather Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The world is facing significant challenges related to the deterioration of air quality, primarily due to high concentrations of emissions from anthropogenic sources such as urbanization, industrialization, and vehicular traffic, this is compounded by a lack of environmental awareness [1,2]. Fireworks displays are a global phenomenon, deeply rooted in familial and social settings [3], and are a habitual practice worldwide during folk, religious, sporting, political events, and holidays. Notable festivities associated with extensive fireworks usage include New Year's Eve, Diwali Festival (India), and Spring Festival (China) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The world is facing significant challenges related to the deterioration of air quality, primarily due to high concentrations of emissions from anthropogenic sources such as urbanization, industrialization, and vehicular traffic, this is compounded by a lack of environmental awareness [1,2]. Fireworks displays are a global phenomenon, deeply rooted in familial and social settings [3], and are a habitual practice worldwide during folk, religious, sporting, political events, and holidays. Notable festivities associated with extensive fireworks usage include New Year's Eve, Diwali Festival (India), and Spring Festival (China) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve vibrant colors, additional components, such as magnesium powder, iron powder, aluminum powder, antimony powder, and inorganic salts, are incorporated into the manufacturing process. Unfortunately, fireworks burning leads to multiple forms of pollution, including noise pollution [ 13 , 14 , 15 ], light pollution, and significant amounts of litter. Furthermore, fireworks release substantial quantities of particulate pollutants and gas pollutants, such as SO 2 and NO x (nitrogen oxides), which significantly contribute to the deterioration of air quality.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al found that a government ban on fireworks burning during the COVID-19 period resulted in effective pollution prevention and control during Diwali [ 44 ]. Parra et al modeled changes in PM 2.5 concentration and observed a decrease, with regards to an earlier fireworks display [ 14 ].…”
Section: Introductionmentioning
confidence: 99%